Cesarean scar endometriosis: presentation of 198 cases and literature review - Ping Zhang; Yabing Sun; Chen Zhang; Yeping Yang; Linna Zhang; Ningling Wang; Hong Xu (BMC, 2019)
Abstract Background Cesarean scar endometriosis (CSE) is the most common type of abdominal wall endometriosis (AWE). The aim of this study was to systematically identify the clinical features of CSE and recommend precautionary measures. Methods A large, retrospective study was undertaken with CSE patients treated surgically at our hospital between January 2005 and December 2017. Results A total of 198 CSE patients were enrolled, with a mean age of 32.0 ± 4.0 years. The main complaint of the patients was abdominal mass (98.5%), followed by cyclic pain (86.9%). The latency period of CSE was 31.6 ± 23.9 months, and the duration between the onset of symptoms and this surgery was 28.3 ± 25.0 months. A majority (80.8%, n = 160) of the patients had undergone a Pfannenstiel incision, and a minority (19.2%, n = 38) a vertical midline incision. The latency period of CSE in the case of a Pfannenstiel incision was significantly shorter than that in the case of a vertical midline incision (24.0 vs 33.0 months, P = 0.006). A total of 187 (94.4%) patients had a single endometrioma, 11 (5.6%) patients had multiple endometriomas, and the 11 multiple-endometrioma patients had all undergone a Pfannenstiel incision. Lesions of endometrioma were common in corner sites, after either incision: 142/171 (83.0%) in Pfannenstiel incision scars and 32/38 (84.2%) in vertical incision scars. Conclusions The findings of this study indicate that the Pfannenstiel incision carries a higher risk of CSE than the vertical midline incision. Thorough cleaning at the conclusion of CS, particularly of both corner sites of the adipose layer and the fascia layer, is strongly recommended for CSE prevention. Further studies might provide additional recommendations.